2014
DOI: 10.1088/0953-8984/26/28/285501
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved synchrotron photoemission and density functional theory on the iridium modified Si(1 1 1) surface

Abstract: The physical and electronic properties of the Ir modified Si(1 1 1) surface have been investigated with the help of angle resolved photoemission spectroscopy and density functional theory. The surface consists of Ir-ring clusters that form a [Formula: see text]reconstruction. A comparison between the measured and calculated band structure of the system reveals that the dispersions of the projected bulk states and the states originating from [Formula: see text] domains are heavily modified due to Umklapp scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The islands are similar in size and shape; however, island in Figure b have SLD’s, whereas the island in Figure a is flat and featureless. The wetting layer surrounding the island is made out of Ir-ring clusters that form domains on Si(111). , Ring clusters consist of a transition metal surrounded by six Si atoms, three of which directly bind to the transition metal and are called bridging adatoms and the remaining three Si atoms, called the capping adatoms bind two bridging adatoms and one Si substrate atom. The Ir/Si(111) system exhibits Stranski–Krastanov-type growth.…”
Section: Resultsmentioning
confidence: 99%
“…The islands are similar in size and shape; however, island in Figure b have SLD’s, whereas the island in Figure a is flat and featureless. The wetting layer surrounding the island is made out of Ir-ring clusters that form domains on Si(111). , Ring clusters consist of a transition metal surrounded by six Si atoms, three of which directly bind to the transition metal and are called bridging adatoms and the remaining three Si atoms, called the capping adatoms bind two bridging adatoms and one Si substrate atom. The Ir/Si(111) system exhibits Stranski–Krastanov-type growth.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Since these substrates are mainly used in semiconductor industry, they can provide a smooth transition from a prototype in a research lab to a consumer product. Some of these structures have high aspect ratios; therefore, they are called nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can still have some surface contribution. Previously, we studied Ir ring clusters on Si(111) surface extensively [37,38]. Ab-initio density functional theory calculations performed on this surface revealed that below the Fermi level, there is a state associated with Ir atoms embedded in the ring clusters.…”
mentioning
confidence: 99%